TEST: Serious games for radio communications learning (2013)
The game industry has suffered an impressive explosion of popularity, becoming the largest entertainment industry in the world. Games have become a sophisticated extension of the reality and an interesting way for complementing human mind utopias. Training software allows the trainee to immerse in quasi-real controlled situations that could be measured by trainers. In this work we discuss the duality existing between the training based on a serious game and a simple game, based on state of the art technologies. Then we show a training system for telecommunications technicians based on a combination between serious games and "traditional" e-learning platform. We show results for a trial made with a group of students from different disciplines (not only engineering) in order to evaluate learning outcomes using serious games versus other learning approaches. In this paper we discuss such results and make a descriptive statistical analysis of the results